CHANGES IN THE INTEGRATION AND INNOVATION OF CULTURAL TOURISM DURING THE YEARS OF INDEPENDENCE: HISTORICAL ANALYSIS - Облоқулов Достон Ўктам ўғли (American Journals, 2023)
This article analyzes the role of museums and historical monuments in the development of tourism in the years of independence, as well as the ongoing reforms in this area on the basis of scientific sources.
Keywords: Tourism, cultural heritage, museum, historical monument, tourism development